2004
DOI: 10.1016/j.neuron.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in the npr-1 Gene Modifies Ethanol Responses of Wild Strains of C. elegans

Abstract: Variation in the acute response to ethanol between individuals has a significant impact on determining susceptibility to alcoholism. The degree to which genetics contributes to this variation is of great interest. Here we show that allelic variation that alters the functional level of NPR-1, a neuropeptide Y (NPY) receptor-like protein, can account for natural variation in the acute response to ethanol in wild strains of Caenorhabditis elegans. NPR-1 negatively regulates the development of acute tolerance to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
183
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(196 citation statements)
references
References 57 publications
6
183
0
Order By: Relevance
“…In some cases, natural variation in a single gene can be identified that affects the regulation of complex yet distinct behavior patterns (e.g., de Bono and Bargmann, 1998;Krieger and Ross, 2002;Davies et al, 2004;Hammock, 2007). Interestingly, a number of recent achievements in this area involve food-related behaviors and the foraging gene, which encodes a cGMP-dependent protein kinase (PKG) (Osborne et al, 1997;Ben-Shahar et al, 2002Hirose et al, 2003;Fitzpatrick and Sokolowski, 2004;Ingram et al, 2005;Fussnecker and Grozinger, 2008;Garabagi et al, 2008;Heylen et al, 2008;Lucas et al, 2009;Lucas and Sokolowski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, natural variation in a single gene can be identified that affects the regulation of complex yet distinct behavior patterns (e.g., de Bono and Bargmann, 1998;Krieger and Ross, 2002;Davies et al, 2004;Hammock, 2007). Interestingly, a number of recent achievements in this area involve food-related behaviors and the foraging gene, which encodes a cGMP-dependent protein kinase (PKG) (Osborne et al, 1997;Ben-Shahar et al, 2002Hirose et al, 2003;Fitzpatrick and Sokolowski, 2004;Ingram et al, 2005;Fussnecker and Grozinger, 2008;Garabagi et al, 2008;Heylen et al, 2008;Lucas et al, 2009;Lucas and Sokolowski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We employed a protocol adapted from a published method 1,13 to estimate internal ethanol concentration following exposure to 500 mM ethanol. The estimate we obtained was 1770.5 mM (n ¼ 3) and close to the published values (e.g., 29 mM 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many biological phenomena contribute to ethanolinduced responses. These include the involvement of neuropeptide-Y related pathways, [1][2][3][4] glutamate receptors, 5,6 GABA receptors, 7,8 the cAMP signalling pathway, 9,10 the BK potassium channel, SLO-1 [11][12][13] , and membrane perturbation. 14 Many genes and proteins are conserved between Caenorhabditis elegans and humans, including many of those that have been identified as playing a possible role in the effects of ethanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregating strains also tend to show higher rates of locomotion on food, preference for thicker portions of the bacterial lawn, and more rapid habituation to ethanol [66,67]. These differences in behaviour are not found in the absence of food.…”
Section: Conservation Of Pkg Function Across Multiple Foraging Behavimentioning
confidence: 92%